A novel method for the analysis of clinical biomarkers to investigate the effect of diet on health in a rat model. Issue 9 (7th May 2015) - Hopes, K.; Cauchi, M.; Walton, C.; MacQueen, H.; Wassif, W.; Turner, C.
<x xml:space="preserve">Abstract</x> We demonstrate differentiation between two diets fed to rats across time via instrumentation combined with multivariate data analysis.